Load Balancing in UDNs Considering the Small-Cell Cluster Layout and the APs Inter-Communications - Salhani, Mohamad (2019 IEEE International Conference on Communication, Networks and Satellite (Comnetsat), 2019)
In Ultra-Dense Networks, the load across the small cells is unevenly distributed due to the random deployment of small cells, the mobility of user equipments (UEs) and the preference of small cells during the selection and reselection. This results in performance degradation. To solve this problem, this paper proposes proactive algorithms for balancing the load across the small-cell clusters and compares their balancing results to the previous reactive algorithms. The proactive algorithms distribute the UEs to the access points (APs), while the reactive algorithms are only triggered when the load of the chosen small-cell cluster reaches a predefined threshold. Moreover, this paper employs the design structure matrix (DSM) method in balancing the load and reducing the inter-communications between the APs. The impact of the small-cell cluster layout on the balancing results is also studied. The results indicate that the proactive algorithm with the DSM method achieves the best balance efficiency and significantly reduces the inter-communications between the APs.